PENGEMBANGAN MEDIA POSKER BAHAYA MINUMAAN BERPEMENIS DALAM KEMASAN SEBAGAI UPAYA PENGENDALIAN DIABETES MELITUS - Djihan Adila; Tati Ruhmawati (Jurnal Kesehatan Siliwangi, 2025)
Background: Indonesia ranked fifth globally with 19.5 million people living with diabetes in 2021. In Cimahi City, West Java, diabetes cases increased by 10,016 in 2023. A preliminary study in RW 12, Utama Subdistrict, South Cimahi, indicated low awareness among patients regarding the health risks associated with sugar-sweetened beverages (SSBs). Objective: This study aimed to develop a calendar-based poster (posker) as an educational tool to raise awareness about the dangers of SSBs and support diabetes mellitus control. Methods: A research and development design using the 4D model (Define, Design, Develop, Disseminate) was employed during March to April 2025. The population included all diabetes patients in RW 12, with a total of 30 participants selected through total sampling. A one-group pretest-posttest design without a control group was used to assess media effectiveness. Result: The Define phase revealed the need for printed educational materials with calendar elements. A posker was developed and validated by experts: material (95%), media (100%), and target users (91%). Post-intervention knowledge scores significantly increased from 54.37 to 88.30 (p = 0.000, Wilcoxon test). In the Dissemination phase, the posker was shared via social media and received positive feedback. Conclusions: The posker is an effective medium for increasing knowledge about the health risks of SSBs and may serve as a practical educational intervention in diabetes management.